Hallway BIM reconstruction - Chi, Kailun (Nanyang Technological University, 2023)
Building Information Modelling Reconstruction for Hallways based on Point Cloud Building Information Modelling (BIM) is a digital representation of a building, including relevant information such as physical and functional characteristics during its life cycle from construction to demolition. It is an approach to interact physical building components inside a virtual environment. Operations such as construction, assembly and maintenance can be tested virtually, and problems met might be solved through discussion prior to a real operation, which enhances safety level. Therefore, BIM can also be considered as a method to increase productivity and reduce the cost for stakeholders, construction teams and residents. Currently, BIM is being developed by a range of countries such as the United States, the United Kingdom, China and Singapore, and it has been used in architecture, engineering, and construction (AEC) industry where collaboration and shared knowledge are commonly required . This report explores the application of deep learning segmentation techniques for the automatic reconstruction of corridors Building Information Modelling (BIM) models from point cloud data. The aim of this research is to enhance the accuracy of corridor BIM reconstruction.